Secular Power, Divine Presence: The Badges of Our Lady of Aarschot - van Asperen, Hanneke (The Mediaeval Journal, 2018)
Abstract This article focuses on the badges of Our Lady of Aarschot (Brabant, Belgium) which entwine secular and religious iconographies through the use of heraldic signs and devices.The cheap mass-produced souvenirs deliver both a religious and a political message reflecting the association of the noblemanWilliam of Croy-Chièvres with the Virgin of Aarschot as well as his relationship with the Habsburg-Burgundian rulers, Charles V in particular.The badges display a combination of different heraldic devices, usually associated with elite culture, indicating that these symbols were widely understood, also among pilgrims from the middle and lower classes who bought these objects. The exploration of influences and purposes underlying the design and production pewter pilgrim badges from one cult site demonstrates how fully these cheap, objects participated in the prevailing, symbolic modes of elite self-fashioning for a broad audience.